2007
DOI: 10.1111/j.1365-2826.2007.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Paracrinicity: The Story of 30 Years of Cellular Pituitary Crosstalk

Abstract: Living organisms represent, in essence, dynamic interactions of high complexity between membrane‐separated compartments that cannot exist on their own, but reach behaviour in co‐ordination. In multicellular organisms, there must be communication and co‐ordination between individual cells and cell groups to achieve appropriate behaviour of the system. Depending on the mode of signal transportation and the target, intercellular communication is neuronal, hormonal, paracrine or juxtacrine. Cell signalling can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
240
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(251 citation statements)
references
References 935 publications
(558 reference statements)
6
240
0
5
Order By: Relevance
“…The interaction with HSPGs should also dimerize such soluble species that are reported to participate in axonal growth (34) and axonal pruning (36). They might also dimerize with membrane-bound APP and ECM binding of soluble forms could increase the local concentration of secreted APP leading to a modulation of its function as demonstrated, e.g., for growth factors (41).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction with HSPGs should also dimerize such soluble species that are reported to participate in axonal growth (34) and axonal pruning (36). They might also dimerize with membrane-bound APP and ECM binding of soluble forms could increase the local concentration of secreted APP leading to a modulation of its function as demonstrated, e.g., for growth factors (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated oestrogen concentrations reduce prolactin inhibitory factor via a negative feedback mechanism, causing a further increase in prolactin (8,33). Prolactin is known to suppress pituitary gonadotropins by slowing GnRH pulse frequency (34,35,36). Slow GnRH pulses preferentially lead to suppression of LH and production of FSH (37).…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary harbors several types of endocrine cells that release their hormone pulses into the systemic blood circulation, with intermingled supportive folliculo-stellate (FS) cells. For many years, two-dimensional histological studies on pituitary sections showed a heterogeneously scattered distribution of endocrine cells throughout the parenchyma, although specific topographic affinities between heterotypical and homotypical hormone-producing cells have been reported (Allaerts et al 1991, Noda et al 2001, Denef 2008. Pituitary cellular organization is now known to be much more ordered than was traditionally recognized.…”
Section: Introductionmentioning
confidence: 99%